The Role of Wearable Technology in Early Detection of Catastrophic Emergencies in Healthcare Services at Patar Asih General Hospital Lubuk Pakam in 2023 - Elaninanivi Br Tarigan (Institut Kesehatan Medistra Lubuk Pakam, 2025)
Wearable technology has become an innovation in modern healthcare services, providing real-time monitoring of patients’ vital signs and supporting early detection of catastrophic emergencies. This study aims to analyze the role of wearable technology in early detection of catastrophic emergencies in healthcare services at Patar Asih General Hospital Lubuk Pakam in 2023. A quantitative descriptive research design was employed involving 120 respondents, consisting of healthcare workers and patients who utilized wearable devices. Data were collected through structured questionnaires and observations, then analyzed using descriptive statistics. The results showed that 78.3% of respondents considered wearable devices highly effective in monitoring patients’ vital signs, while 72.5% of healthcare workers reported that these devices facilitated faster responses in emergency conditions. Additionally, 81.7% of respondents agreed that wearable technology increased hospital preparedness in dealing with catastrophic emergencies. However, several obstacles were identified, such as limited device availability, maintenance costs, and the need for training in device utilization. The findings indicate that